Asymptomatic Colonic Anisakiasis: Is It So Rare? - Tetsuro Takasaki; Toru Yamada; Junji Kinoshita; Yasuaki Motomura (Case Reports in Gastroenterology, 2020)
Most cases of anisakiasis occur in the stomach. Colonic anisakiasis, especially when asymptomatic, is extremely rare. We report a case of asymptomatic colonic anisakiasis and present a literature review of cases of colonic anisakiasis. A 52-year-old man underwent colonoscopy for colorectal cancer screening. Although no colorectal neoplasm was found, an Anisakis larva was detected in the transverse colon and the larva was removed by grasping forceps. Our review of PubMed revealed that 40% of cases of colonic anisakiasis are asymptomatic. We conclude that asymptomatic colonic anisakiasis may not be as rare as conventionally assumed.